The mediating effect of mood spectrum on the relationship between autistic traits and catatonia spectrum - Dell’Osso, Liliana; Amatori, Giulia; Carpita, Barbara; Massimetti, Gabriele; Nardi, Benedetta; Gravina, Davide; Benedetti, Francesca; Bonelli, Chiara; Casagrande, Danila; Luciano, Mario; Berardelli, Isabella; Brondino, Natascia; et al. (Frontiers in Psychiatry, 2023)
Background: In the recent years, several studies have shown a correlation between autism spectrum disorder (ASD) and catatonia. It is also known that both conditions are found to be associated with mood disorders. This study aimed to investigate the relationship between autistic traits and catatonic symptoms, as well as the potential mediating role of mood disorder spectrum in the relationship between them. Methods: The total sample of 514 subjects was composed by four diagnostic groups, composed by patients affected by catatonia (CTN), borderline personality disorder (BPD), major depressive disorder (MDD) and healthy controls (HC). Subjects were assessed with the SCID-5-RV, the Adult Autism Subthreshold Spectrum (AdAS Spectrum) and the Catatonia Spectrum (CS) and the Mood Spectrum Self-Report (MOODS-SR). Statistical analyses included Pearson's coefficient calculation, multiple linear regression, and mediation analysis. Results: all the correlations appear to be strongly positive and significant with the strongest coefficient emerging between AdAS Spectrum total score and CS total score (r=0.762, p<0.001). The Mediation Analysis showed that AdAS Spectrum total score showed a significant indirect effect on CS total score through MOODS-SR total score (b=0.168, 95% bootstrapped CI [0.127:0.207]). Conclusions: The present study highlights the presence of a mediating role of the mood disorder spectrum in the relationship between autistic traits and the catatonia spectrum.